2014
DOI: 10.1038/ejhg.2014.246
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide inbreeding estimation within Lebanese communities using SNP arrays

Abstract: Consanguineous marriages have been widely practiced in several global communities with varying rates depending on religion, culture, and geography. In consanguineous marriages, parents pass to their children autozygous segments known as homozygous by descent segments. In this study, single-nucleotide polymorphisms were analyzed in 165 unrelated Lebanese people from Greek Orthodox, Maronite, Shiite and Sunni communities. Runs of homozygosity, total inbreeding levels, remote consanguinity, and population admixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In fact, consanguineous marriages and same-religion marriages are widely practiced in the Middle East region and particularly in Lebanon where the population is divided into different religious groups. Jalkh et al , showed a high prevalence of rare recessive diseases in offspring of related and unrelated couples in Lebanon, which is concordant with the data presented in our study [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, consanguineous marriages and same-religion marriages are widely practiced in the Middle East region and particularly in Lebanon where the population is divided into different religious groups. Jalkh et al , showed a high prevalence of rare recessive diseases in offspring of related and unrelated couples in Lebanon, which is concordant with the data presented in our study [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with documented cultural preferences for first-cousin matings in some contemporary societies. 60,61 This raises the question of whether the differential rates of consanguinity among present-day Central versus West Eurasia could be traced back in time. In fact, we observed an excess of individuals with F ROH > 0.0117 in Central versus West Eurasia among ''advanced complex agriculturalists,'' roughly spanning third to first millennium BC, depending on region (odds ratio = 5.1, p = 0.009; Table 1; Data S1C).…”
Section: Reportmentioning
confidence: 99%
“…In addition, a detailed family tree was drawn up by the trained interviewer. It is important to note that in highly consanguineous populations, such as the UK Pakistani community, genomic studies have shown that even couples who declare themselves to be unrelated are homozygous at a proportion of gene loci, due to consanguineous unions in ancestral generations (Jalkh et al, 2015).…”
Section: Methodsmentioning
confidence: 99%